2023
DOI: 10.1007/s11604-023-01448-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of image quality, arterial depiction, and radiation dose between two rapid kVp-switching dual-energy CT scanners in CT angiography at 40-keV

Abstract: Purpose To compare the quantitative parameters and qualitative image quality of dual-energy CT angiography (CTA) between two rapid kVp-switching dual-energy CT scanners. Materials and methods Between May 2021 and March 2022, 79 participants underwent whole-body CTA using either Discovery CT750 HD (Group A, n = 38) or Revolution CT Apex (Group B, n = 41). All data were reconstructed at 40-keV and with adaptive statistical iterative reconstruction-Veo of 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Using low keV VMI enhances iodinated contrast in the image, enabling iodine dose reduction. Multiple studies have recently shown the interest of using 40 keV VMI to improve diagnostic accuracy and image quality in different vascular settings and with different CT detector technologies such as dual source, dual layer and fast kVp switching ( 23 25 ). In a phantom study, up to 40%–60% iodine reduction could be achieved without loss in image quality ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using low keV VMI enhances iodinated contrast in the image, enabling iodine dose reduction. Multiple studies have recently shown the interest of using 40 keV VMI to improve diagnostic accuracy and image quality in different vascular settings and with different CT detector technologies such as dual source, dual layer and fast kVp switching ( 23 25 ). In a phantom study, up to 40%–60% iodine reduction could be achieved without loss in image quality ( 26 ).…”
Section: Introductionmentioning
confidence: 99%